1990
DOI: 10.1016/0304-3959(90)91158-f
|View full text |Cite
|
Sign up to set email alerts
|

Study of verbal description in neuropathic pain

Abstract: The aim of this paper is to study the quality of verbal description and its diagnostic value in neuropathic pain. The verbal description of pain as assessed by a French adjective list questionnaire (QDSA) is compared between a group of 100 patients with neuropathic pain and a mixed group of 97 chronic benign and cancer non-neuropathic pain patients. Seventeen descriptors of the 61 QDSA descriptors have a significant intergroup frequency difference. By principal component analysis and Varimax rotation of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(98 citation statements)
references
References 22 publications
4
85
0
9
Order By: Relevance
“…Both questionnaires appear to address a coherent phenotype in patients with knee OA, despite the aforementioned differences in pain classifications. MPQ PRI scores exhibited similar associations with painDETECT, S‐LANSS, and measures of pain severity, possibly because the MPQ considers neuropathic‐like as well as nociceptive‐like characteristics 2, 33.…”
Section: Discussionmentioning
confidence: 86%
“…Both questionnaires appear to address a coherent phenotype in patients with knee OA, despite the aforementioned differences in pain classifications. MPQ PRI scores exhibited similar associations with painDETECT, S‐LANSS, and measures of pain severity, possibly because the MPQ considers neuropathic‐like as well as nociceptive‐like characteristics 2, 33.…”
Section: Discussionmentioning
confidence: 86%
“…Three of them reported in the early phase of the disease and 4 in the late stage. Burning pain in feet and legs, paresthesias in the legs, shooting, dysaesthesic and leg pain were seen in 16 (57.1%) patients, suggesting neuropathic pain, according to Boureau 20 and Bouhassira et al 21 verbal descriptors. Most of them (14 patients) presented it in the early phase of the condition.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover in our series, most of the patients complained of pain in the early phase of TSP/HAM, as also shown in other series 6,[26][27][28] and this may correlate with predominant inflammatory activity in this phase 23,29 . According to Boureau 20 and Bouhassira et al 21 verbal descriptors, nociceptive and neuropathic pain symptoms have been identified in the description of TSP/HAM patients, by previous authors, as shown below.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Pain characteristics were quantified using the McGill Pain Questionnaire (MPQ) and the University of California and San Francisco (UCSF) Pain Service questionnaire (Melzack, 1983;Fields, 1987). Patients were asked to complete upper body pain charts using different graphical symbols for numbness, pins and needles, burning, stabbing and ache (Boureau et al, 1990). Free-text sections were included for women to describe their experience with pain, limitations of daily activities and coping strategies.…”
Section: Questionnaire Designmentioning
confidence: 99%